PENGARUH LATIHAN PENGUATAN OTOT KUADRISEP TERHADAP PENURUNAN RASA NYERI PADA PENDERITA OSTEOARTHRITIS LUTUT: TINJAUAN PUSTAKA SISTEMATIS DAN META ANALISIS - Muhammad Tauvan Aqshadila, (2021)
Knee osteoarthritis is a degenerative disease of the joints due to damaged cartilage. The main symptom that people with knee osteoarthritis often complain about is knee pain. Muscle therapy can relieve or minimize that symptom. Currently, research on muscle strengthening exercises has been widely researched, with that being said comprehensive discussion based on previous research is very important to add to references related to muscle strengthening exercises in the therapy of knee osteoarthritis. This research method uses a systematic literature review, in other words, a method of collecting literature through PubMed and Google Scholar, then an assessment of the eligibility of the journal to answer research questions that are the focus of the researcher. The literature is based on clinical trials in patients with knee osteoarthritis using experimental and observational research designs. Based on the analysis of 7 studies of quadriceps muscle strengthening exercises in patients with knee osteoarthritis, they showed significant and higher improvements than respondents who used standard therapy such as taking drugs and physiotherapy. Additional therapies such as quadriceps strengthening exercises can be the first alternative option in a osteoarthritis therapy program.